2007
DOI: 10.1007/bf02980270
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative and photo-protective effects of coumarins isolated fromFraxinus chinensis

Abstract: Free radicals and reactive oxygen species (ROS), which are generated by UV irradiation, may cause serious injury to skin cell membranes, DNA and functional proteins. In addition, these agents stimulate the expressions of matrix metalloproteinases (MMPs), which can degrade most components of the extracellular matrix (ECM), including collagen. In order to develop new anti-photoaging agents, five major components from the extract of Fraxinus chinensis extract (FCE) were identified. Two of the major components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…Aesculin, one of the simplest coumarins known to have multiple pharmacological and biochemical activities, is an established inhibitor of lipoxygenase and cyclo-oxygenase and shows scavenging effects on ROS [13] . It has been reported that aesculetin has chemo-preventive and anti-tumor activities in vivo against cancer [5,14] and also induces apoptosis in several types of human cancer cells by diverse pathways [1,6,7,15,16] . Hence, it is a great challenge to determine the complex structure-activity relationships between aesculin/ aesculetin and their metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aesculin, one of the simplest coumarins known to have multiple pharmacological and biochemical activities, is an established inhibitor of lipoxygenase and cyclo-oxygenase and shows scavenging effects on ROS [13] . It has been reported that aesculetin has chemo-preventive and anti-tumor activities in vivo against cancer [5,14] and also induces apoptosis in several types of human cancer cells by diverse pathways [1,6,7,15,16] . Hence, it is a great challenge to determine the complex structure-activity relationships between aesculin/ aesculetin and their metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Further more, this compound shows an inhibitory effect on BOP-induced oxidative DNA damage and carcinogenesis in a hamster pancreatic tumor model [2] , as well as chemo-preventive [3] and anti-tumor activity on cancer [4] . Aesculin and aesculetin have strong antioxidative and photo-protective activities, by scavenging 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radicals and superoxide anions from the xanthine/xanthine oxidase system and inhibiting oxidation of 5-(6-)-chloromethyl-2', 7'-dichlorodihydro-fluorescein diacetate [5] . Aesculetin increases apoptosis of 3T3-L1 adipocytes in a time-and dose-dependent manner [6] , and inhibits cell growth and cell cycle progression by inducing G1 phase arrest in HL-60 leukaemia cells, which is a direct result of the inhibition of retinoblastoma protein phosphorylation [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, coumarins possess antioxidant activities, probably due to their structural analogy with flavonoids and benzophenones [21] . For example, esculetin isolated from the cortex of Fraxius chinensis showed anti-photoaging activity through anti-oxidant activities [22] . Coumarins in plants are present in the free form or glycosides, and are emerging as potent therapeutic drugs for free radical-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…UV-induced MMPs degrade the connective tissue of the skin, thereby impairing the structural integrity of the dermis. Such accumulative ECM protein damage acts as a major contributor to the formation of wrinkles, reduction of elasticity, and drooping of skin [9].…”
Section: )mentioning
confidence: 99%
“…Moreover, they can interfere and alter protein functions, increase lipid peroxidation, damage genes, and promote diseases and aging [9]. Figure.…”
Section: Dpph Free Radical-scavenging Activity Of the Threementioning
confidence: 99%